MADNESS AND METHOD: APPROACHES TO THE HISTORY OF MENTAL ILLNESS - Swartz, Sally (PINS-Psychology in Society, 2025)
In the past fifteen years a number of histories of colonial psychiatry and the colonial insane in Africa have appeared. These include Megan Vaughan’s influential “The madman and the medicine men” in Curing their ills: Colonial power and African illness (1991); Jock McCulloch’s Colonial Psychiatry and “The African Mind” (1995); Jonathan Sadowsky’s Imperial Bedlam: Institutions of madness in colonial southwest Nigeria (1999); Robert Edgar and Hilary Sapire’s African apocalypse: The story of Nontetha Nkwenkwe, a twentieth-century South African prophet (2000); Lynette Jackson’s Surfacing up: Psychiatry and social order in colonial Zimbabwe, 1908-1968 ( 2005); and now Julie Parle’s States of mind: Searching for mental health in Natal and Zululand, 1868-1918 (2007). There are also growing numbers of scholarly articles and chapters in books on colonial asylums in and beyond South Africa (see for example, Swartz, 1995a & 1995b; Deacon, 1996; Marks, 1999; Keller, 2001). This small industry is parallel to, and has features in common with a large body of work on the history of psychiatry, insanity, and lunatic asylums in Europe and the US. Historians and social scientists have puzzled over a set of recurring themes, including classification systems and their use in the management of people regarded as mentally ill; economic and social factors underlying the dramatic growth of asylum populations from the mid nineteenth century; treatment regimes; and the slow professionalisation of mad-doctoring in relation to growing asylum populations. Histories of asylums and psychiatry have provided a complex and welcome context for studies of twentieth-century psychiatry, the de-institutionalisation movement, and a variety of perspectives on the psychiatric industry. Michel Foucault’s Madness and civilisation (1989:274) in which he argues that the “stammered dialogue between madness and reason” was interrupted by a “great confinement” – a sweeping analysis of the impulse to segregate lunatics from society - has provided a provocative counterpoint to detailed histories of specific asylums in particular social contexts.